Identification of a telomere-binding activity from yeast. - Berman, J (1986)
In yeast, the ends of the chromosomes (telomeres) terminate in repeated poly(C1-3A) sequences. We have identified a yeast activity that binds specifically to these poly(C1-3A) repeats. An agarose gel binding assay was used to detect and characterize this activity in cell extracts using both cloned telomere DNA and yeast genomic DNA as substrates. The activity appears to bind specifically to poly(C1-3A) sequences, despite their different primary sequences, yet does not bind specifically to telomeric repeats, such as poly(C4A2), poly(C4A4), and poly (C1-8T) from other lower eukaryotes.